Conservación de órganos. - Jiménez Penick, F.J.; Moreno Sierra, Jesús; Redondo González, E.; Resel, Luis; Silmi Moyano, A.; Bocardo Fajardo, Gloria (Clínicas Urológicas de la Complutense, 1999)
Sin resumen